اليات انشاء مؤسسات ناشئة لخريجي معاهد علوم و تقنيات النشاطات البدنية و الرياضية - زغواني, نور الاسلام; د.برباخ, رابح (معهد علوم وتقنيات النشاطات البدنية والرياضية بالمسيلة, 2023)
اليات انشاء مؤسسة ناشئة للمقبلين على التخرج في معاهد علوم وتقنيات النشاطات البدنية والرياضية وتهدف الدراسة التي بين أيدينا إلى محاولة معرفةاليات انشاء مؤسسة ناشئة للمقبلين على التخرج في معاهد علوم وتقنيات النشاطات البدنية والرياضية، ولأجل ذلك اتبعنا المنهج الوصفي، حيث تكونت عينة الدراسة من 35 طالب وطالبة، واستعملنا لجمع البيانات استمارة الاستبيان، واستخدمنا لتحويل البيانات الى نتائج إحصائية معامل (الصدق، الثبات، معامل الارتباط البسيط لبيرسون)، وجاءت أهم نتائج الدراسة ان النسبة الأكبر منالطلبة والتي تمثل 94%يرون أن الدولة لا تعطي دعما وتسهيلات مالية لكل المؤسسات الناشئة الرياضية، وانه من الضروري امتلاك موارد مالية كافية ومطابقة مع مقتضيات المنافسة وذات علاقة مع أنشطة المؤسسة الرياضية الناشئة، اما اهم الاقتراحات والتوصيات فتمثلت بداية بوضع رؤية مشتركة لتشجيع الابتكار للطلبة الجامعيين، وتكييف النظام القانوني والضريبي مع الشركة الناشئة وحاملي المشاريع المبتكرة والمستثمرين. الكلمات الدالة:المؤسسات الناشئة، الخريجون من المعاهد.  عنوان الدراسة :ماهي اليات انشاء مؤسسة ناشئة للمقبلين على التخرج في معاهد علوم وتقنيات النشاطات البدنية والرياضية؟  أهداف الدراسة :الكشف عنالياتانشاءمؤسسةناشئةللمقبلين على التخرج منمعاهدعلوموتقنياتالنشاطاتالبدنيةوالرياضية.  التعرف على مدى نقص التمويل لدى المقبلين على التخرج من معهد علوم وتقنيات النشاطات البدنية والرياضية لإنشائهم مؤسسة رياضية ناشئة.  ابراز دور نقص الخبرة والامكانيات لدىالمقبلين على التخرج من معهد علوم وتقنيات النشاطات البدنية والرياضية على مدى إنشائهم لمؤسسة رياضية ناشئة.  إيضاح المشاكل التي تواجه المقبلين على التخرج من معهد علوم وتقنيات النشاطات البدنية والرياضية والعراقيل الإدارية لإنشاء مؤسسة رياضية ناشئة.  التساؤل العام الدراسة :ماهي اليات انشاء مؤسسة ناشئة للمقبلين على التخرج في معاهد علوم وتقنيات النشاطات البدنية والرياضية؟ التساؤلات الجزئية :  هل يؤثر نقص التمويل لدى المقبلين على التخرج في معهد علوم وتقنيات النشاطات البدنية والرياضية لإنشائهم مؤسسة رياضية ناشئة؟  هل يؤثر نقص الخبرة والامكانيات لدى المقبلين على التخرج في معهد علوم وتقنيات النشاطات البدنية والرياضية على إنشائهم مؤسسة رياضية ناشئة؟  هل يواجه المقبلون على التخرج في معهد علوم وتقنيات النشاطات البدنية والرياضية عراقيل إدارية وقانونية لإنشاء مؤسسة رياضية ناشئة؟ الفرضية العامةللدراسة :  هناك اليات انشاء مؤسسة ناشئة للمقبلين على التخرج في معاهد علوم وتقنيات النشاطات البدنية والرياضية. الفرضيات الجزئية  يؤثر نقص التمويل لدى المقبلين على التخرج في معهد علوم وتقنيات النشاطات البدنية والرياضية لإنشائهم مؤسسة رياضية ناشئة  يؤثر نقص الخبرة والامكانيات لدى المقبلين على التخرج في معهد علوم وتقنيات النشاطات البدنية والرياضية على إنشائهم مؤسسة رياضية ناشئة.  يواجه المقبلون على التخرج في معهد علوم وتقنيات النشاطات البدنية والرياضية عراقيل إدارية وقانونية لإنشاء مؤسسة رياضية ناشئة. المنهج المتبع في الدراسة : الوصفي الأدوات المستخدمة في الدراسة الاستبيان جاءهذاالبحثفيفصول . الفصلالأول:الاطار العام للدراسة وتناولالفصلالثاني:المؤسسات الناشئة أماالفصلالثالث.خريجي الجامعات الفصلالرابع: منهجية الدراسة منأهمالنتائجالتيتوصلإليهاالباحث :من خلال دراستنا لموضوع "اليات انشاء مؤسسة ناشئة لخريجي معاهد علوم وتقنيات النشاطات البدنية والرياضية"، وكذا دراستنا الميدانية التي أجريناها على طلبة معهد علوم وتقنيات النشاطات البدنية والرياضية، وبعد تحميل وعرض النتائج المتحصل عليها ومن خلال التحليل الإحصائي المتحصل عليه استطعنا الوصول إلى عدة نتائج:  النسبة الأكبر منالطلبة والتي تمثل 94%يرون أن الدولة لا تعطي دعما وتسهيلات مالية لكل المؤسسات الناشئة الرياضية،  من الضروري امتلاك موارد مالية كافية ومطابقة مع مقتضيات المنافسة وذات علاقة مع أنشطة المؤسسة الرياضية الناشئة،  يرى الطلبة أنه ليس لديهم ما يكفي من المادة الأولية من مال ويد عاملة لبدء مشروعهم الخاص أو مؤسستهم الرياضية،  يرون أنه وجب عليهم البحث في النماذج الجديدة خاصة في التعامل مع إنشاء مؤسسة ناشئة والابتكار عامة حتى ولو توفرت لديهم الخبرة،  النسبة الأكبر من الطلبة والتي تمثل 86% يرون أن نقص الإمكانيات المادية خاصة الأجهزة والمعدات "الأدوات والأجهزة الرياضية والمنشآت والملاعب وكافة التجهيزات الرياضية" قد يؤثر على إنشائهم لمؤسساتهم الخاصة،  يرى أن القوانين المالية والتدعيمية في صالح الطالب المتخرج لتسهيل مهمة إنشاء المؤسسة الرياضية الناشئة. أهم التوصيات:في حدود ما توصلنا من نتائج وكذا حدود البحث الموضوعة نقترح ما يلي:  وضع رؤية مشتركة لتشجيع الابتكار للطلبة الجامعيين،  تكييف النظام القانوني والضريبي مع الشركة الناشئة وحاملي المشاريع المبتكرة والمستثمرين،  تنفيذ تدابير تمويل فعالة للباحثين ورجال الأعمال والشركات الناشئة،  فتح الأسواق العمومية والاستراتيجية للشركات الناشئة وتسهيل القوانين للطلبة الخريجين،  تحفيز رجال الاعمال والمستثمرين لتمويل الشركات المبتكرة ذات الإمكانات العالية تشجيع ثقافة الابتكار والمؤسسات الناشئة؛  إنشاء أنظمة تحفيزية لتشجيع نشاط شركات ناشئة واعدة في الجزائر. Searchlight in English Faculty Institute of Sciences and Sports and Technical and PhysicalActivities Department: Order No:sports management and administration No. d 'registration :171733059514 Searcher :zaghouani nour el islam Title of the thesis (dissertation):mechanism for establishing a start up. Language of the thesis: arabic Model of the thesis: master 2 Country: REPUBLIC OF ALGERIA-M'SILA University: University of M'sila Surname and first name of the supervisor Grade: Lecturer Number of pages: 92 Summary: Title of the study:mechanism for establishing a start up. The purpose of the study:Disclosure of the mechanisms for establishing an emerging institution for those who are about to graduate from the Institutes of Science and Technology of Physical and Sports Activities. Problem: With the economic, technological and other developments, projects have multiplied and diversified, and competition has increased in the national, international and global market as a whole, and so-called emerging enterprises have appeared. A committee has been established in Algeria to define conditions and advantages that must be met in emerging enterprises. In return, within the framework of the state’s endeavor to support the establishment and development of these emerging enterprises, it has established mechanisms and structures that contribute to providing the necessary funding, including the National Agency for Supporting Youth Employment, the National Agency for the Management of Microcredit. , venture capital firms and venture capital firms. (Saqr, 2019, p. 56) This study seeks to clarify the mechanisms of establishing an emerging institution for graduates of the Institutes of Science and Technology of Physical and Sports Activities, by answering the following problem that came to the mind of the researcher:  What are the mechanisms for establishing an emerging institution for those who are about to graduate from the Institutes of Science and Technology of Physical and Sports Activities? Hypotheses: Does the lack of funding affect those who are about to graduate from the Institute of Science and Technology of Physical and Sports Activities to establish an emerging sports institution?  Does the lack of experience and capabilities of those who are about to graduate from the Institute of Science and Technology of Physical and Sports Activities affect their establishment of an emerging sports institution?  Do those about to graduate from the Institute of Science and Technology of Physical and Sports Activities face administrative and legal obstacles to establishing an emerging sports institution? - The most important results achieved are: Through our study of the topic "Mechanisms of establishing an emerging institution for graduates of the Institutes of Science and Technology of Physical and Sports Activities", as well as our field study that we conducted on the students of the Institute of Science and Technology of Physical and Sports Activities, and after downloading and presenting the obtained results and through the obtained statistical analysis, we were able to reach several results:  The largest percentage of students, which represents 94%, believes that the state does not give support and financial facilities to all emerging sports institutions.  It is necessary to have sufficient financial resources that are compatible with the requirements of the competition and related to the activities of the emerging sports institution,  The students see that they do not have enough raw materials of money and labor to start their own project or sports institution.  They believe that they should research new models, especially in dealing with establishing a startup and innovation in general, even if they have experience.  The largest percentage of students, which represents 86%, believes that the lack of material capabilities, especially devices and equipment, “sports tools and devices, facilities, playgrounds and all sports equipment” may affect their establishment of their own institutions,  He believes that the financial and supportive laws are in the interest of the graduated student to facilitate the task of establishing the emerging sports institution
Keywords: المؤسسات الناشئة; الخريجون من المعاهد; اليات انشاء مؤسسة ناشئة